Intensive home support for mental health crises: experience of the Trieste territorial crises team, in Italy - Rossana Maria Seabra Sade; Serena Goljevscek; Clarissa Mendonça Corradi-Webster (Universidade de São Paulo, 2020)
Abstract Early management of mental health crises is important for a good prognosis and treatment adherence. Ideas have been proposed to address crisis situations at home, aiming to reduce hospitalizations and medication doses and to increase care satisfaction. Identifying experiences of home care for mental health crises can support managers and professionals in proposing innovative practices. This article aims to describe the experience of Trieste, in Italy, which implemented a home crisis team service. The work is carried out in four phases: application of the inclusion criteria for treatment by the crisis team; initial assessment; co-construction of the therapeutic plan; discharge and transition to other services. In one year, the team performed 124 assessments and provided care for 59 people. Regarding psychiatric symptoms, 93% of the patients showed significant improvement at discharge. Considering overall functioning, 81% showed significant improvement. Data show a reduction of compulsory admission rates of 29.4% in the first semester of 2018 and of 78.8% in the second semester, compared to 2017. The home crisis team achieved its goals of holistically caring for suffering individuals and reducing their contact with hospitals.